Algorithm Development for the Optimum Rainfall Estimation Using Polarimetric Variables in Korea. (24th May 2015) - You, Cheol-Hwan; Lee, Dong-In
Abstract : In this study, to get an optimum rainfall estimation using polarimetric variables observed from Bislsan radar which is the first polarimetric radar in Korea, rainfall cases for 84 hours caused by different conditions, which are Changma front and typhoon, Changma front only, and typhoon only, occurred in 2011, were analyzed. And rainfall algorithms were developed by using long period drop size distributions with six different raindrop axis ratio relations. The combination of the relations between R and Z, Z DR, R and K DP, Z DR, and R and K DP with different rainfall intensity would be an optimum rainfall algorithm if the reference of rainfall would be defined correctly. In the case the reference is not defined adequately, the relation between R and Z, Z DR, K DP, A H and R and Z, K DP, A H can be used as a representative rainfall relation. Particularly if the qualified Z DR is not available, the relation between R and Z, K DP, A H can be used as an optimum rainfall relation in Korea.